Association of Cutaneous Manifestations with Undiagnosed Diabetes Mellitus in Adults: Cutaneous Manifestations with Undiagnosed Diabetes Mellitus - Zubair, Muhammad; Gillani, Aneela; Malik, Muhammad Khan; Niazi, Saira; Perveen, Zahida; Bano, Asma (Pakistan Journal of Health Sciences, 2025)
Diabetes mellitus (DM) remains underdiagnosed in resource-limited settings, where access to laboratory screening is constrained. Cutaneous manifestations may serve as visible, cost-effective indicators. Objectives: To determine the association between characteristic skin lesions (acanthosis nigricans, skin tags, xerosis) and undiagnosed diabetes in adults. Methods: A cross-sectional study involving 400 participants was conducted at a Teaching Hospital with adult patients without known diabetes (aged 18–70) attending dermatology and general medicine clinics. Detailed dermatological examinations documented predefined skin manifestations, while biochemical assessments (fasting plasma glucose, HbA1c, and oral glucose tolerance test) classified participants into normoglycemic, pre-diabetic (IFG/IGT), or diabetic groups per ADA criteria. Statistical analysis was done on SPSS version 26.0. Results: The prevalence of cutaneous markers was significantly higher in prediabetes and diabetes groups (p<0.001). Acanthosis nigricans was present in 61.4% of cases, nearly eight times more prevalent than in normoglycemic individuals (8.1%). Similarly, multiple skin tags (≥5) affected 52.9% of diabetics compared to just 12.4% of controls, while xerosis showed a fourfold increase from 9.5% in normoglycemic subjects to 44.3% in diabetics. Conclusions: It was concluded that specific dermatological manifestations exhibit a robust correlation with undiagnosed diabetes and pre-diabetes. Incorporating cutaneous markers into routine clinical examinations may enhance early detection, particularly in resource-limited settings.